2023
DOI: 10.1002/chem.202303073
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Non‐Solvated Dialkylalumanyl Anion and XPS Characterization of Al(I) and Al(II) Species**

Satoshi Kurumada,
Ryotaro Yamanashi,
Kengo Sugita
et al.

Abstract: A non‐solvated alkyl‐substituted Al(I) anion dimer was synthesized by a reduction of haloalumane precursor using a mechanochemical method. The crystallographic and theoretical analysis revealed its structure and electronic properties. Experimental XPS analysis of the Al(I) anions with reference compounds revealed the lower Al 2p binding energy corresponds to the lower oxidation state of Al species. It should be emphasized that the experimentally obtained XPS binding energies were reproduced by delta SCF calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Although the above data clarifies the connectivity of 2 and 4 , the electronic structure is somewhat ambiguous because both Al and V atoms have similar electronegativity (Al: 1.61, V: 1.63, Pauling) and flexibility in their oxidation states . Polarization of the V–Al bond in 2 would have three possibilities as described in Figure a.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the above data clarifies the connectivity of 2 and 4 , the electronic structure is somewhat ambiguous because both Al and V atoms have similar electronegativity (Al: 1.61, V: 1.63, Pauling) and flexibility in their oxidation states . Polarization of the V–Al bond in 2 would have three possibilities as described in Figure a.…”
Section: Results and Discussionmentioning
confidence: 99%
“…15 Earlier this year Yamashita and co-workers also reported that non-solvated dialkylaluminyl anion can be isolated from the mechanochemical reduction of the dialkylaluminium iodide with an Na/K alloy ( IV ). 16…”
mentioning
confidence: 99%